Influencia del cuidado espiritual que brinda el profesional de enfermería en el estado de ánimo, nivel de colaboración y signos vitales de los pacientes hospitalizados en la unidad de cuidados intensivos del Hospital Nacional Guillermo Almenara Irigoyen - Bullón López, Gloria Orietta (2019)
Objective: To determine the influence of spiritual care provided by nursing professionals in the mood, level ofcooperation and vital signs of patients hospitalized in the Intensive Care Unit at the Guillermo Almenara IrigoyenGeneral Hospital. Methodology: The study design was quantitative, quasi-experimental, because it worked withtwo groups of patients, an experimental group which was provided with spiritual care and a control group that wasnot given this type of care. Previously, 8 nurses were trained to participate in the spiritual care, using a module “Spiritual Care for the Critical Patient “ developed by the authors. As a data collection instrument, an observationguide was used which validity was measured through expert opinion and reliability using Cronbach’s test. Thecollected data were processed using the SPSS 15.0 statistical software. Results: In the experimental group, prior toreceiving spiritual care, 60% of patients showed a bad mood and 30% a good mood. After receiving spiritual care the 100% of patients in the experimental group had a mood between very good and good. In the control group inan initial assessment 100% of the patients had a mood between bad and very bad in the final evaluation; 100% hada poor mood. In the experimental group prior to receiving spiritual care, 60% of the patients showed a bad level ofcooperation and 30% a good level. After receiving spiritual care the 100% of patients had a level of cooperationbetween very good and good. In the control group in the initial evaluation 80% of patients had a bad cooperationlevel. In the final evaluation 50% showed a poor level of cooperation and the same percentage showed a good levelof cooperation. In the experimental group, 90% did not modify their vital functions after receiving spiritual support.In the control group 70%, in the same way, did not modify their vital functions in the final evaluation. However, it isobserved that 30% of the control group improved their vital functions and only 10% improved in the experimentalgroup. Conclusions: Spiritual care positively affects mood and level of cooperation of patients in the ICU with asignificance level of 0.000 for the experimental group. However, it does not have influence on the vital functions ofpatients in the ICU, reaching a level of significance greater than 0.05 in the experimental group